Differential effects of migration networks: The case of China. (July 2017) - Liang, Zai; Li, Zhen; Morooka, Hideki
The crucial role of migration networks in the process of migration has been well established. The main goal of our paper is to examine the role of migration networks in the case of China, a country that has had the largest migrant population in human history. Specifically, we focus on issues that have received relatively little attention in the migration literature. We first examined how the use of migration networks differs for individuals with different characteristics such as education, gender and household registration ( hukou ) status. Based on the migration literature, we generated a set of hypotheses. We then examined the use of migration networks by people with different characteristics both in the context of migration departure (initiation of migration) and destination choice, using the micro-data from the 2000 China Population Census. Our results show that female migrants, migrants without local hukou, and younger migrants are more likely to rely on well-developed migration networks, whereas the most educated migrants are less likely to depend on them. We also found that migration networks are more important for floating migrants than for permanent migrants.